2023
DOI: 10.1002/smll.202208260
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Buried Interface with Piperazine Dihydriodide Layer for High Performance Inverted Solar Cells

Abstract: comparison to stability between both kinds of solar cells, we might soberly conceive that there is still an immense challenge for the operation lifetime of PSCs. [8][9][10][11] Up to this point, significant attempts have been made to increase the stability of PSCs using multiple-faceted tactics such as adjusting the components of perovskite precursor (methylammounium(MA)free, inorganic or low dimensional materials), [12][13][14] developing additive engineering or passivation agents, [15,16] exploring novel fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…Also, the intermediate PDI 2 buffer layer reduces the adhesion of PTAA substrate, and the system adapts itself to the lattice mismatch between the perovskite and the substrate, thus forming a voids-free buried interface (Figure 17c−f). 219 In other words, the active Ni ≥3+ ions on the NiO x surface are effectively suppressed by this method, and the cavity extraction capacity is greatly improved. Moreover, the perovskite films formed on the BDT-POZ-modified NiO x showed a smoother and more uniform surface and no pinholes than a standard NiO x HTL.…”
Section: The Interface Engineering Of Perovskite/htl Interfacementioning
confidence: 99%
“…Also, the intermediate PDI 2 buffer layer reduces the adhesion of PTAA substrate, and the system adapts itself to the lattice mismatch between the perovskite and the substrate, thus forming a voids-free buried interface (Figure 17c−f). 219 In other words, the active Ni ≥3+ ions on the NiO x surface are effectively suppressed by this method, and the cavity extraction capacity is greatly improved. Moreover, the perovskite films formed on the BDT-POZ-modified NiO x showed a smoother and more uniform surface and no pinholes than a standard NiO x HTL.…”
Section: The Interface Engineering Of Perovskite/htl Interfacementioning
confidence: 99%
“…8f). Liang et al 101 introduced a piperazine dihydrotriamine (PDI 2 ) buffer layer between PTAA substrate and the perovskite. The PDI 2 buffer layer can promote the matching of thermal expansion between the perovskite and the substrate, resulting in a decrease in the adhesion of the PTTAA substrate, and promote the matching of the PTAA substrate with the perovskite lattice, resulting in the release of the lattice strain, thus forming a void-free buried interface.…”
Section: Management Of Interlaminar Stressmentioning
confidence: 99%
“…Therefore, with the benefits of a favorable interface and defect passivation under the (P3CT-BN) buffer layer, the hole transport ability of P3HT is enhanced, resulting in an increase in PCE% from 13.13% to 19.23%. Qi Song et al [147] recently reported that the PCE of PSCs was improved to 23.42% by adding a buffer layer comprised of piperazine dihydride (PDI 2 ) at the embedded bottom interface (Figure 8c). The PDI 2 buffer layer proved effective in addressing the thermal expansion mismatch between the perovskite layer and the substrate coated with PTAA HTL.…”
Section: Buffer Layers At Htl/perovskite Interfacementioning
confidence: 99%
“…Reproduced with permission. [147] Copyright 2023, Wiley. d) Energy level alignment diagram for PSCs with and without KBr buffer layer modification, and the PL spectra for various concentration KBr buffer layer modification.…”
Section: Buffer Layers At Htl/perovskite Interfacementioning
confidence: 99%